Effect of a commercial enzyme (nutrase) on growth performance of growing pigs fed diets containing dried distillers grains with solubles - Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,076 pigs (PIC 337 × C22, initially 87.4 lb) were used to determine the effect of a commercial enzyme product on the growth performance of pig fed diets containing dried distillers grains with solubles (DDGS). Pigs were randomly allotted to 1 of 3 treatments balanced by average initial BW within gender. There were 13 replicate pens (7 barrow and 6 gilt pens) per treatment. Treatments included: (1) diet with 3% added fat (control); (2) diet supplemented with enzyme with only 2% added fat but formulated to have an energy content equal to that of the control diet on the basis of calculated increased ME from the enzyme (Nutrase; Nutrex, Lille, Belgium); and (3) diet with 2% added fat without enzyme formulated using the same energy values for the control diet (low energy). Diets were corn-soybean meal-based, contained DDGS, and were fed in 3 phases (87 to 130 lb, 130 to 185 lb, and 185 to 210 lb BW for Phases 1, 2, and 3, respectively). Thirty percent DDGS was included in diets from 87 to 185 lb, and 15% DDGS was included in the last phase from 187 to 210 lb. The control and Nutrase dietary treatments were balanced to a constant lysine:calorie ratio at 2.69, 2.29, and 1.97 g/Mcal ME for Phases 1, 2, and 3, respectively, whereas the low energy dietary treatment had calculated lysine:calorie ratios of 2.73, 2.32, and 2.00 g/Mcal ME for Phases 1, 2, and 3, respectively. There were no treatment × gender interactions (P > 0.25) observed for any response criteria evaluated. The expected differences (P > 0.03) in growth performance between barrows and gilts were observed in all periods and overall. Barrows had greater ADG, ADFI, and final weight but poorer F/G compared with gilts. Except for the poorer F/G (P < 0.01) of pigs fed the enzyme treatment compared with pigs fed diets without enzyme from d 0 to 28, there were no differences among treatments for ADG (P > 0.70), ADFI (P > 0.77), and F/G (P > 0.66) at any of the periods or for the overall study. In conclusion, under the conditions of the present experiment, the commercial enzyme used at the manufacturer’s recommended level did not affect growth performance of growing pigs fed diets containing DDGS.
Keywords: Dried distillers grains with solubles; Enzyme; Swine